2014
DOI: 10.1016/j.celrep.2014.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Crypt Formation in the Uterus for Embryo Homing and Implantation Requires Wnt5a-ROR Signaling

Abstract: Summary Embryo homing and implantation occur within a crypt (implantation chamber) at the antimesometrial (AM) pole along the uterus. The mechanism by which this is achieved is not known. Here we show that villi-like epithelial projections from the main uterine lumen towards the AM pole at regularly spaced intervals to form crypts for embryo implantation were disrupted in mice with uterine loss or gain of function of Wnt5a, or loss of function of both Ror1 and Ror2. This disruption of Wnt5a-ROR signaling resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
132
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 40 publications
(64 reference statements)
4
132
1
1
Order By: Relevance
“…48,49 This timely remodeling of junction complexes under the control of ovarian steroid hormones represents a decreased epithelial apicalbasal polarity during uterine receptivity establishment. 9,11,45 In fact, previous studies have demonstrated a lack of transition of the luminal epithelium from a high to a less apical-basal polar state in the absence of uterine Msx1 and 2 genes hampers blastocyst implantation. 9 As a small GTPase, Rac1 has been found crucial in regulating cell shape and epithelial polarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48,49 This timely remodeling of junction complexes under the control of ovarian steroid hormones represents a decreased epithelial apicalbasal polarity during uterine receptivity establishment. 9,11,45 In fact, previous studies have demonstrated a lack of transition of the luminal epithelium from a high to a less apical-basal polar state in the absence of uterine Msx1 and 2 genes hampers blastocyst implantation. 9 As a small GTPase, Rac1 has been found crucial in regulating cell shape and epithelial polarity.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, there is recent evidence showing that either excessive decrease or maintenance of epithelial polarity upon loss or gain of Wnt5a disrupts uterine epithelial projections, crypt formation and thus normal implantation. 11 Localized to the apical surfaces of many epithelia, the ERM proteins are essential for establishing apical identity and architecture across many organisms. 31 Previous expression studies have revealed that ERM proteins are spatiotemporally expressed in the implanting mouse uterus and human endometrium, 34,52 suggesting that ERM signaling may participate in constructing the cellular architecture necessary for blastocyst activation and uterine receptivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found differential expression of WNT ligands upon E2 and Prog treatment in both mouse and human EMOs, comparable with previous in vivo reports. In mice, Wnt5a and Wnt7a, which are upregulated upon Prog treatment, increase at estrous when Prog levels start to rise (Miller et al, 1998), and are described as being important for glandular differentiation as well as for preparing a receptive environment for blastocyst implantation (Cha et al, 2014;Miller et al, 1998). In humans, WNT5A and WNT7A were found to be downregulated and the WNT inhibitor WIF1 was upregulated during the proliferative phase (Punyadeera et al, 2005;Talbi et al, 2006), comparable to the reversed findings in human EMOs after Prog treatment (reflecting the secretory phase), showing upregulation of WNT5A and WNT7A (although the latter not significantly) and downregulation of WIF1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We observe dynamic changes in the architecture of the uterine lumen surrounding implantation. We highlight the utility of this method by studying implantation defective Wnt5a mutants, as previously characterized by molecular marker expression, defective crypt formation and embryonic lethality (Cha et al, 2014). Our method reveals defects in the folding pattern of Wnt5a mutant uteri that cannot be discerned by traditional histology.…”
Section: Introductionmentioning
confidence: 99%